2013
DOI: 10.1021/jz4019207
|View full text |Cite
|
Sign up to set email alerts
|

Autoxidation of Organic Compounds in the Atmosphere

Abstract: We present a hypothesis that autoxidation (inter- and intramolecular hydrogen abstraction by peroxy radicals) plays an important role in the oxidation of organic compounds in the atmosphere, particularly organic matter associated with aerosol. In the laboratory, we determine the rate of this process at room temperature for a model system, 3-pentanone. We employ ab initio calculations to investigate H-shifts within a broader group of substituted organic compounds. We show that the rate of abstraction of hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
726
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 557 publications
(787 citation statements)
references
References 57 publications
26
726
1
1
Order By: Relevance
“…Oxygenated compounds contribute most of the mass flux due to the combined effect of their larger molecular weight from the incorporation of oxygen during oxidation (73), and the propensity for less-volatile and more-water-soluble compounds to deposit. The oxidant deposition observed by our instrument is attributed to hydroperoxides (−OOH), although we are missing the likely minor contribution of methyl hydroperoxide (MHP).…”
Section: Resultsmentioning
confidence: 99%
“…Oxygenated compounds contribute most of the mass flux due to the combined effect of their larger molecular weight from the incorporation of oxygen during oxidation (73), and the propensity for less-volatile and more-water-soluble compounds to deposit. The oxidant deposition observed by our instrument is attributed to hydroperoxides (−OOH), although we are missing the likely minor contribution of methyl hydroperoxide (MHP).…”
Section: Resultsmentioning
confidence: 99%
“…An important characteristic of the organic molecules participating in nucleation is their high oxygen content and consequently low vapor pressure. The formation of these highly oxygenated molecules (HOMs) has been described by Ehn et al (2014), who found that, following the well-known initial steps of α-pinene ozonolysis through a Criegee intermediate leading to the formation of an RO 2 · radical, several repeated cycles of intramolecular hydrogen abstractions and O 2 additions produce progressively more oxygenated RO 2 radicals, a mechanism called autoxidation (Crounse et al, 2013). The (extremely) low volatility of the HOMs results in efficient NPF and growth, even in the absence of sulfuric acid .…”
Section: Introductionmentioning
confidence: 99%
“…The formation of ELVOCs possibly involves intramolecular isomerization of RO 2 radicals. 30,[32][33][34][35] There is growing evidence that oligomers play a key role in initial particle formation from large alkenes because of their predicted very low vapor pressures. 19,36 In ozonolysis experiments where SCI were scavenged using small acids or water, particle nucleation was shown to be suppressed, suggesting that the oligomers formed from SCI were potentially the nucleating precursors.…”
Section: Introductionmentioning
confidence: 99%